Santini and Italy. Proceedings from the international conference Rome, Accademia Nazionale di San Luca - Palazzo Carpegna, 6th-7th June 2023 - Kalina, Pavel; (eds.) Roca De Amicis Augusto (Univerzita Palackého v Olomouci, 2024)
This book contains proceedings of the international conference Santini and Italy, held in Rome in June 2023. In his contribution, Augusto Roca de Amicis describes the nature of the structural relations of Santini's work to Italian architecture. Pavel Kalina discusses the development of Santini scholarship in the art historical literature of the 20th and early 21st centuries. Richard Biegel shows in his contribution that the sources of Santini's work can be found not only in Italian but also in French architecture. Michael Young's text points to the connection between Santini's architecture and contemporary literary theory and practice, which blended different languages and styles. In his article, Ulrich Fürst stresses the importance of a sense of originality for the design of the Benedictine monastery church at Rajhrad, whose construction demonstrated its independence from the monastery of Břevnov, for which the Dientzenhofers worked. Johana Bronková explores the relationship between Santini's architecture and the work of the great Italian architect Francesco Borromini. Marisa Tabarrini presents a completely new discovery - the unknown plans of Santini's church of St. Peter and Paul in Prague's Zderaz. Important for understanding the functioning of Baroque buildings is the article by Jakub Řehak, who analyses the water and ventilation system of the monastery in Plasy. On the other hand, Madleine Riedenklau's text is devoted to the literature on the monastery and church in Sedlec. Irena Bukačová introduces the reader to the past and present of the pilgrimage site in Mariánská Týnice.
Keywords: Architektura